Development of Accessible Museum for Blind Tourists: A Case Study in Museum of The Asian African Conference - Fernando, Willionel Dhimas; Rizal, Edwin; Yuliawati, Ayu Krishna (The Center for Disability Studies and Services Brawijaya University, 2022)
As we know that museums store a lot of visual objects. So that blind people who do not have vision will have difficulty enjoying the visual objects of the museum. This study discusses the tourist attractions of the museum that can be enjoyed by blind tourists. To support this research, a qualitative research method with a case study approach was used. The results showed that blind tourists enjoyed museum attractions in two ways, hearing and touching. Information will be received by listening to museum educators explain stories about visual objects. Then to add information, blind tourists can touch the visual object. Accessibility that needs to be developed in Museum of the Asian African Conference is guiding block, braille, and audio media. Museum educators can be trained to be able to guide blind tourists properly.